Performance of Major Millet Crops in Tamil Nadu : An Economic Analysis - Narmadha, N.; Kandeepan, A. (Arthshastra Indian Journal of Economics & Research, 2017)
The present study aimed at analyzing the performance of major millets in Tamil Nadu. The paper analyzed the growth rates, instability, and decomposition analysis of area, production, and productivity of major millets during the period from 1970-71 to 2011 -15 .The study period was divided into Period I (1970 to 1991) and Period II (1991 to 2015). The compound growth rate results showed that the growth rate in area and production for most of the millet crops, with the exception of maize, showed a negative growth rate. The instability indices revealed that during the Periods I and II, the instability was high. The differentiation occurred in millet production due to the area for most of the millet crops, and area and productivity for some of the millet crops. Thus, there was an immediate need of policies in order to increase the area under millet crops in Tamil Nadu so as to increase the millet production.